Investigation of flow visualization and droplet vaporization in enclosed chamber - Poh, Cai Jia (Nanyang Technological University, 2020)
In a compressor, moving bodies are present for it to work. However, friction between two moving bodies relative to each other will produce heat energy. This heat needs to be cooled to sustain the efficiency of the compressor. In a conventional compressor, lubricant is used to lubricate, cool or seal the its internal components. Due to the dependence on lubricant in the design, such compressors are considered to have poor compactness and low portability. In addition, the fluid in such compressors are contaminated by the lubricant, hence the usage of such compressor in the processing of food and beverage are limited. To solve the limitation of lubrication, liquid injection can be used as an alternative method to cool the internal temperature of the compressor and the heat energy produced by friction. In order study the effectiveness of liquid droplet injection, an enclosed chamber was used to simulate the compression chamber of the compressor. The enclosed chamber will then be subjected to a liquid injection where the vaporization of liquid droplets will occur causing a drop in temperature. To study the effectiveness of numerical simulation, the numerical simulation of droplet vaporization in an enclosed chamber using the Discrete Phase Model (DPM) in ANSYS Fluent. The simulation results show injecting liquid droplets in an enclosed chamber is effective as the temperature of the enclosed chamber dropped by 21.25%. However, more comprehensive simulation study is necessary to account for the change in pressure of the compression chamber and wall heating.